Safe, strong & streetwise - Benedict, Helen (Boston : Little, Brown, 1987)
Section titles include "Who Would Hurt You and Why," "Your Sexual Rights and Responsibilities," "Protecting Yourself Inside," "Self-defense," and "Getting Help." Includes an appendix for parents.
Keywords: Child sexual abuse -- United States -- Juvenile literature; Child sexual abuse -- United States -- Prevention -- Juvenile literature; Sexual abuse; Sexual abuse -- Prevention; Safety